مدى توافر سمات القيادة التحويلية لدى القيادات الإدارية وأثرها في تحقيق رؤية المملكة 2030 "دراسة تطبيقية في جامعة شقراء" - Alaklobee, Ayed (مجلة العلوم الإدارية و الإقتصادية, 2019)
The study aims to identify the availability of transformational leadership features, recognize the most practiced transformational leadership features, identify the nature of the relationship between transformational leadership features and the Kingdom Vision (2030), and verify the impact of transformational leadership features in achieving the vision of the Kingdom (2030) and the impact of demographical qualities on the practice of transformational leadership among the administrative leaders of Shaqra University. In order to achieve the objectives of the study, the study used the analytical descriptive method and developed two hypotheses. The list of questionnaire developed to measure the study variables was distributed among the administrators of the university through a random relative sample of (232) from the study population (1738). By using the Alpha Kronbach parameter, the variables of the study were confirmed. Descriptive statistical methods and multiple regression were used to test the study hypotheses. The study found that the impact of transformational leadership features in its four dimensions was about (71.5 %) in achieving the vision of the Kingdom (2030). The influence of the role model was about (0.34), the impact of the inspirational motivation was about (0.17) and the impact of individual intellectual stimulus on the achievement of the vision of the Kingdom 2030 was about (0.05). The impact of the individual interest on the achievement of the vision is equal to (0.12). There are differences in the averages between males and females in the ideal impact, the inspirational motivation, and the individual attention. There are significant differences in all dimensions of transformational leadership due to the age of the surveyed, while there are no significant differences due to the number of years of experience and educational level of the surveyed.